Theoretical study of dipyridine phenanthrene derivatives for BHJ organic solar cells application: a DFT approach - Xhibo, Finesa; Biswas, Joydeep; Datta, Bandita (SPRINGER, 2021)
The topic of organic solar cells is emerging thanks to their promising properties being low-cost, lightweight and most importantly, eco-friendly. Optimization of active layers has a crucial role in maintaining and improving the efficiency of solar cells. In this study, we investigated the photovoltaic effects of eight novel derivatives for organic solar cells application. The study was based on the pi-conjugated donor-acceptor (D-A) structure. The studied molecules act as donors, whereas the PCBM is the acceptor. The studied dipyridine phenanthrene derivatives differ by various functional groups at both terminals. The dipyridine phenanthrene derivatives, abbreviated as DiPP1 to DiPP8, consist of phenanthrene as the core, 2-vinylpyridine as the conjugated pi-bridge and two terminal functional groups (viz., -OH, -NO, -Cl, -NH2, -NO2, -CN, -COOH, -COOCH3, -COCH3). In this work, DFT and TD-DFT applying B3LYP/6-311G(d) and WB79XD/6-311G(d) levels of theories were employed with the Gaussian 09W programme. Geometries and optoelectronic properties were studied by analyzing HOMO energy (E-HOMO), LUMO energy (E-LUMO), bandgap energy (E-gap), open-circuit voltage (V-oc) and light-harvesting efficiency (LHE) to test their applicability in solar cells.
Keywords: Density functional theory; Dipyridine phenanthrene derivatives; Light-harvesting efficiency; Open-circuit voltage; Bulk heterojunction; Solar cell; TO-ROLL FABRICATION; PHOTOVOLTAIC PROPERTIES; POLYMER-FULLERENE; SMALL MOLECULES; DESIGN; DONOR; Chemistry